Analisis Nilai Tambah Tepung Tapioka Menggunakan Metode Hayami dan Strategi Pengembangan Produk Sisa Menggunakan Metode Analisis SWOT : Studi Kasus PD. Mekar Jaya Garut - Pamungkas, Arif Maulanan; Cahyadi, Ujang; Taptajani, Dedi Sa'dudin (Jurnal Kalibrasi, 2025)
This research was conducted to determine the added value of tapioca flour waste/by-products (ongok) and their contribution to the company in Ciwangi Village, Limbangan, Garut—whether it is profitable enough, and to explore the potential of these by-products as a breakthrough for a new product, namely kerupuk elod. The study used the Hayami method and SWOT analysis. The Hayami method was used to calculate added value by involving input and output, and by considering several key factors in value-added analysis such as technical and market factors, as well as supporting concepts like conversion factors, labor coefficients, and output value. SWOT analysis was used to determine the company’s position and to formulate appropriate development strategies.The research results showed that the feasibility of the tapioca flour business at PD. Mekar Jaya is profitable, with a profitability of 11%, indicating a gain. The R/C Ratio obtained was 1.31, indicating business efficiency. The NPV was IDR 373,601,200, confirming the project's viability. The BEP was IDR 448,486,270 in monetary terms and 4,555.94 kg in unit terms. The added value or profit obtained was IDR 9,839,900, with an added value ratio of 49%. The recommended development strategy for PD. Mekar Jaya’s by-product utilization includes government support for building waste processing facilities, directing waste processing toward value-added products, and developing a variety of cassava-based and cassava-waste-based products.